Hubungan Kecerdasan Emosional Dengan Prestasi Belajar Mahasiswa Semester Ii Bimbingan Konseling UIN Ar-Raniry - Fauziah Fauziah (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2015)
Emotional Intelligence and Learning Achievement. The purpose of this study was to determine the relationship of emotional intelligence and academic achievement second semester students Guidance konselin UIN Ar-Raniry. This type of research is an analytic description with degrees kecepercayaan 95%. The population is all second level students Major of Counseling is 78 students. These results indicate a significant relationship between emotional intelligence and academic achievement were proved with ap value of 0.001